Central Precocious Puberty Caused by Novel Mutations in the Promoter and 5′-UTR Region of the Imprinted MKRN3 Gene - Fanis, Pavlos; Skordis, Nicos; Toumba, Meropi; Papaioannou, Nikoletta; Makris, Anestis; Kyriakou, Andreas; Neocleous, Vassos; Phylactou, Leonidas A. (Frontiers in Endocrinology, 2019)
Background: Central Precocious Puberty (CPP) is clinically defined by the development of secondary sexual characteristics before the age of 8 years in girls and 9 years in boys. To date, mutations in the coding region of KISS1, KISS1R, PROKR2, DLK1 and MKRN3 genes have been reported as causative for CPP. This study investigated the presence of causative mutations in both the promoter and the 5’-UTR regions of the MKRN3 gene. Methods: Sanger DNA sequencing was used for screening the proximal promoter and 5’-UTR region of the MKRN3 gene in a group of 73 index girls with CPP. Mutations identified were cloned in luciferase reporter gene vectors and transiently transfected in GN11 cells in order to check for changes in the activity of the MKRN3 promoter. GN11 cells were previously checked for Mkrn3 expression using lentivirus mediated knock-down. In silico analysis was implemented for the detection of changes in the mRNA secondary structure of the mutated MKRN3 5’-UTR. Results: Three novel heterozygous mutations (-166, -865, -886 nt upstream to the transcription start site) located in the proximal promoter region of the MKRN3 gene were identified in six non-related girls with CPP. Four of these girls shared the -865 mutation, one the -166 and another one the -886. A 5’-UTR (+13 nt downstream to the transcription start site) novel mutation was also identified in a girl with similar clinical phenotype. Gene reporter assay evaluated the identified promoter mutations and demonstrated a significant reduction of MKRN3 promoter activity in transfected GN11 cells. In silico analysis for the mutated 5’-UTR predicted a significant change of the mRNA secondary structure. The minimum free energy (MFE) of the mutated 5’-UTR was higher when compared to the corresponding wild-type indicating less stable RNA secondary structure. Conclusion: Our findings demonstrated novel genetic alterations in the promoter and 5’-UTR regulatory regions of the MKRN3 gene. These changes add to another region to check for the etiology of CPP.